Pattern formation in viscous flows : the Taylor-Couette problem and Rayleigh-Bénard convection - Meyer-Spasche, Rita (International series of numerical mathematics ;, 1999)
The Taylor-Couette system is one of the most studied examples of fluid flow exhibiting the spontaneous formation dynamical structures. In this book the variety of timeindependent solutions with periodic spatial structure is numerically investigated by solution of the Navier-Stokes equations.